2022
DOI: 10.21037/tcr-22-787
|View full text |Cite
|
Sign up to set email alerts
|

High expression of hypoxia-inducible factor 1-alpha predicts poor prognosis in pancreatic ductal adenocarcinoma: a meta-analysis and database validation protocol

Abstract: Background: Hypoxia-inducible factor 1-alpha (HIF-1α) is overexpressed in pancreatic ductal adenocarcinomas (PDACs). However, the prognosis of high expression of HIF-1α in PDACs remains controversial because of lacking a solid support. A meta-analysis may help for a better understanding of the role of HIF-1α in the prognosis of PDACs.Methods: By using a systematic approach, we conducted a meta-analysis from current literature. We performed an advanced search in PubMed, Embase, Cochrane Library and Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Besides, the hyperoxia signaling pathway is involved in aggressive tumor behavior (21), and the GAPDH gene contains a hypoxia response element with a hypoxia inducible factor-1 (HIF-1) transcription factor binding site. By activating HIF-1, the expression of enzymes involved in glycolysis, such as GAPDH, could be enhanced by p-AKT in cancer cells of the colon, kidney and liver (22)(23)(24). Corresponding to this, our analysis of KEGG pathways identified "Glycolysis/ gluconeogenesis" and "HIF-1 signaling pathway" as the enriched hits.…”
Section: Disease Free Survival (Gapdh)mentioning
confidence: 69%
“…Besides, the hyperoxia signaling pathway is involved in aggressive tumor behavior (21), and the GAPDH gene contains a hypoxia response element with a hypoxia inducible factor-1 (HIF-1) transcription factor binding site. By activating HIF-1, the expression of enzymes involved in glycolysis, such as GAPDH, could be enhanced by p-AKT in cancer cells of the colon, kidney and liver (22)(23)(24). Corresponding to this, our analysis of KEGG pathways identified "Glycolysis/ gluconeogenesis" and "HIF-1 signaling pathway" as the enriched hits.…”
Section: Disease Free Survival (Gapdh)mentioning
confidence: 69%
“…Since the induction of hypoxia factor 1α (HIF-1α) expression by hypoxia, Western blotting was used to evaluate the effect of HA-MnO 2 –CDs on improving tumor cell hypoxia. Compared with the control group, the HIF-1α protein bands on the surface of cells coincubated with HA-MnO 2 –CDs were narrower and lighter in color (Figure d), indicating a lower HIF-1α protein content on their surface.…”
Section: Resultsmentioning
confidence: 99%
“…Although the amount of intracellular green fluorescence in the MnO 2 group was less than that in the HA-MnO 2 −CDs group, it was still higher than that in the CDs group, which was related to the Fenton-like reaction of Mn 2+ . 56 These indicated that the intracellular ROS production rate of HA-MnO 2 −CDs was much higher than that of HA-MnO 2 and CDs, providing a Since the induction of hypoxia factor 1α (HIF-1α) expression by hypoxia, 57 Western blotting was used to evaluate the effect of HA-MnO 2 −CDs on improving tumor cell hypoxia. Compared with the control group, the HIF-1α protein bands on the surface of cells coincubated with HA-MnO 2 −CDs were narrower and lighter in color (Figure 6d), indicating a lower HIF-1α protein content on their surface.…”
Section: Preparation and Characterization Of Ha-mno 2 −mentioning
confidence: 99%
“…In the study by Zoa et al published in this issue of TCR , the contributions of HIF1α expression to outcome in PDAC are reported ( 11 ). The authors performed a systematic search for publications that report HIF1α expression (by immunohistochemistry) and clinical data, and performed a meta-analysis on the key outcome variables from 11 publications including 764 patients.…”
mentioning
confidence: 99%
“…These limitations notwithstanding, the work by Zoa et al ( 11 ) is a solid basis from which to initiate follow-up research. The link between HIF1α and poor outcome has been further consolidated, which will hopefully accelerate the development of clinically applicable inhibitors or biomarkers to guide current treatments, for instance radiation.…”
mentioning
confidence: 99%